Chemical constituents from Luxemburgia nobilis (EICHL) - Carvalho Mário G. de; Oliveira Márcia C. C. de; Werle Alceni A. (Journal of the Brazilian Chemical Society, 2000)
Chromatographic fractionation of the hexane extract from the branches of Luxemburgia nobilis (Ochnaceae) afforded beta-sitosterol, stigmasterol, betulinic acid, linoleic acid, methyl-14-methylpentadecanoate, 13-epimanoyl oxide, hexadecanoic acid, tetraeicosanoic acid, hexaeicosanoic acid, the depside atranorin (1) and two new triglycerides (2 and 3). The structures were defined by IR, MS and ¹H- and 13C-NMR spectral analysis involving comparison with literature data. The FAB-MS spectra analysis of the thiomethyl ethers (4 and 5) were used to define the structures of the triglycerides.